Remnant cholesterol predicts cardiovascular disease beyond LDL and ApoB: a primary prevention study. (19th July 2021) - Quispe, Renato; Martin, Seth Shay; Michos, Erin Donelly; Lamba, Isha; Blumenthal, Roger Scott; Saeed, Anum; Lima, Joao; Puri, Rishi; Nomura, Sarah; Tsai, Michael; Wilkins, John; Ballantyne, Christie Mitchell; et al.
Abstract: Aims: Emerging evidence suggests that remnant cholesterol (RC) promotes atherosclerotic cardiovascular disease (ASCVD). We aimed to estimate RC-related risk beyond low-density lipoprotein cholesterol (LDL-C) and apolipoprotein B (apoB) in patients without known ASCVD. Methods and results: We pooled data from 17 532 ASCVD-free individuals from the Atherosclerosis Risk in Communities study ( n = 9748), the Multi-Ethnic Study of Atherosclerosis ( n = 3049), and the Coronary Artery Risk Development in Young Adults ( n = 4735). RC was calculated as non-high-density lipoprotein cholesterol (non-HDL-C) minus calculated LDL-C. Adjusted Cox models were used to estimate the risk for incident ASCVD associated with log RC levels. We also performed discordance analyses examining relative ASCVD risk in RC vs. LDL-C discordant/concordant groups using difference in percentile units (>10 units) and clinically relevant LDL-C targets. The mean age of participants was 52.3 ± 17.9 years, 56.7% were women and 34% black. There were 2143 ASCVD events over the median follow-up of 18.7 years. After multivariable adjustment including LDL-C and apoB, log RC was associated with higher ASCVD risk [hazard ratio (HR) 1.65, 95% confidence interval (CI) 1.45–1.89]. Moreover, the discordant high RC/low LDL-C group, but not the low RC/high LDL-C group, was associated with increased ASCVD risk compared to the concordant group (HR 1.21, 95% CI 1.08–1.34). Similar results were shown when examining discordance across clinical cutpoints. Conclusions: In ASCVD-free individuals, elevated RC levels were associated with ASCVD independent of traditional risk factors, LDL-C, and apoB levels. The mechanisms of RC association with ASCVD, surprisingly beyond apoB, and the potential value of targeted RC-lowering in primary prevention need to be further investigated. Graphical Abstract: